Long term effect of erythromycin therapy in patients with chronic Pseudomonas aeruginosa infection. Issue 12 (December 1995) - Fujii, T; Kadota, J; Kawakami, K; Iida, K; Shirai, R; Kaseda, M; Kawamoto, S; Kohno, S
Abstract : BACKGROUND--Diffuse panbronchiolitis is a chronic infection of the lower respiratory tract common among the Japanese people, with a persistent Pseudomonas aeruginosa infection in the late stage and sustained neutrophil retention in the airways. The long term effect of erythromycin was examined retrospectively in a group of patients with diffuse panbronchiolitis, with and without P aeruginosa infection, and the relationship between drug-induced bacterial clearance and clinical improvement was investigated. METHODS--The history, daily volume of sputum, type of organisms in sputum cultures, pulmonary function tests, arterial blood gas tensions, and chest radiographs were compared in 16 patients with diffuse panbronchiolitis with P aeruginosa infection and 12 without. The total and differential cell counts in the bronchoalveolar lavage (BAL) fluid were compared in 14 of the 28 patients (five of whom were infected with P aeruginosa) before and after 1-12 months of treatment with erythromycin (600 mg/day). The outcome of treatment in patients showing clearance of organisms on repeated sputum cultures was compared with that in those demonstrating persistence of bacteria in the sputum and patients with normal flora. RESULTS--Erythromycin improved respiratory function and arterial blood gas tensions irrespective of the presence or absence of P aeruginosa in the sputum. Treatment also resulted in a reduction in the BAL fluid total cell count and the percentage of neutrophils in both groups of patients. There were no differences between patients in whom the bacteria cleared and those with persistent bacteria or patients with a normal flora with regard to the degree of improvement of respiratory function, arterial blood gas tensions, and BAL fluid cell composition. CONCLUSION--The results suggest that the efficacy of erythromycin in diffuse pan-bronchiolitis may be due to anti-inflammatory effect, independent of P aeruginosa infection or bacterial clearance.